Nano-Computed Tomography: Technique and Applications - Kampschulte, M.; Langheinirch, A. C.; Sender, J.; Litzlbauer, H. D.; Althöhn, U.; Schwab, J. D.; Alejandre-Lafont, E.; Martels, G.; Krombach, G. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Nano-computed tomography (nano-CT) is an emerging, high-resolution cross-sectional imaging technique and represents a technical advancement of the established micro-CT technology. Based on the application of a transmission target X-ray tube, the focal spot size can be decreased down to diameters less than 400 nanometers (nm). Together with specific detectors and examination protocols, a superior spatial resolution up to 400 nm (10 % MTF) can be achieved, thereby exceeding the resolution capacity of typical micro-CT systems. The technical concept of nano-CT imaging as well as the basics of specimen preparation are demonstrated exemplarily. Characteristics of atherosclerotic plaques (intraplaque hemorrhage and calcifications) in a murine model of atherosclerosis (ApoE (-/-)/LDLR(-/-) double knockout mouse) are demonstrated in the context of superior spatial resolution in comparison to micro-CT. Furthermore, this article presents the application of nano-CT for imaging cerebral microcirculation (murine), lung structures (porcine), and trabecular microstructure (ovine) in contrast to micro-CT imaging. This review shows the potential of nano-CT as a radiological method in biomedical basic research and discusses the application of experimental, high resolution CT techniques in consideration of other high resolution cross-sectional imaging techniques.Key Points:• Nano-computed tomography is a high resolution CT-technology for 3D imaging at sub-micrometer resolution.• The technical concept bases on a further development of the established ex-vivo-micro-CT technology.• By improvement of the spatial resolution, structures at a cellular level become visible (e.g. osteocyte lacunae).Citation Format:• Kampschulte M, Langheinirch AC, Sender J et al. Nano-Computed Tomography: Technique and Applications. Fortschr Röntgenstr 2016; 188: 146 – 154
Keywords: nano-CT; vasculature; bone; 3 D imaging